Development of Science E-Modules on the Functions of Living Organs Topic to Improve Science Literacy for Elementary School Students - Muslih, Lindawati; Supardi, Zainul Arifin Imam; Budijastuti, Widowati (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
This study aims to develop a Science E-Module on the material of the locomotor functions of living things to improve the literacy of elementary school students. In this study, the development of e-modules is guided by the 4-D Thiagarajan development model. The development stage includes defining, designing, developing, and distributing (dessiminate) but at the dessiminate stage it is not done completely. The subjects of this research are students of SDN Simomulyo with details of class 5F Â as many as 15 people and class 5H as many as 15 people. Study This will be carried out in the odd semester of the 2021/2022 academic year . Results In this study, it was shown that the device developed in this study met the criteria of validity, practicality, and effectiveness. The validity of learning tools includes conceptual validity, device readability, and the level of difficulty of the device. The practicality of learning tools includes the implementation of learning and constraints during learning activities. The effectiveness of learning includes an increase in learning outcomes, students, student activities during the learning process, and student responses to learning activities. Based on the fulfillment of validity criteria, practicality criteria, and effectiveness criteria, the learning tools developed are suitable for use in learning.